Pengembangan Cimenteng Sebagai Ekowisata di Kota Cimahi - Enok Maryani; Zia Kemala; Farras Fahira Firdaus (Manajemen dan Pariwisata, 2023)
Tourism has now become one of the leading sectors that plays a role in improving the regional economy. The existence of a regional tourism industry sector can support other economic sectors for local communities where tourist attractions are located. Based on the profits obtained from the large number of tourists visiting tourist attractions in an area, local governments need to develop tourism objects. The development of tourism objects is carried out for the advancement of regional tourism, one example is the development of Cimenteng ecotourism in the Cimahi area. This research aims to determine the feasibility of Cimenteng Ecotourism and to find out what factors must be developed to make it an attractive ecotourism. This type of research is qualitative research. The data required is primary data and secondary data obtained from interviews with the help of research instruments in the form of questionnaires to key informants. The resource persons in this research were Cimenteng Ecotourism guards, Cimahi Tourism Office representatives, and community representatives. The data collection technique was carried out in stages in the form of observation, literature study, interview and documentation. Data analysis was carried out using data triangulation techniques and qualitative data analysis. Qualitative data analysis techniques are carried out using the stages of data reduction, data presentation and drawing conclusions. The research results show that the implementation of Cimenteng Ecotourism development as a tourist attraction in Cimahi City is in accordance with the main principles of ecotourism development, namely conservation value, educational value, community participation value and economic value. The Cimenteng Ecotourism development scheme can be seen in the condition of the components in the form of accessibility, amenities, attractions, accommodation and activities.